Signaling Proteins Recruited to the Sperm Binding Site: Role of β-Catenin and Rho A - Wang, Huizhen; Kinsey, William H. (Frontiers in Cell and Developmental Biology, 2022)
Sperm interaction with the oocyte plasma membrane triggers a localized response in the mouse oocyte that leads to remodeling of oocyte surface as well as the underlying cortical actin layer. The recent demonstration that PTK2B is recruited and activated at the sperm binding site raised the possibility that multiple signaling events may be activated during this stage of fertilization. The present study demonstrated that β-catenin and Rho A were recruited to the cortex underlying bound/fused sperm. To determine whether sperm-oocyte contact was sufficient to initiate β-catenin recruitment, Cd9-null and PTK2b-null oocytes were tested for the ability to recruit β-catenin to sperm binding sites. Both Cd9 and Ptk2b ablation reduced β-catenin recruitment raising the possibility that PTK2B may act downstream of CD9 in the response to sperm binding/fusion. Further immunofluorescence study revealed that β-catenin co-localized with f-actin in the interstitial regions between actin layer fenestrae. Rho A in contrast was arranged underneath the actin layer in both the fenestra and the interstitial regions suggesting that they may play different roles in the oocyte.